Confining for Stability: Heterogeneous Catalysis with Transition Metal (Oxide) Nanoparticles Confined in the Secondary Pore Network of Mesoporous Scaffolds. Issue 4 (14th March 2017) - Ciotonea, Carmen; Mazilu, Irina; Dragoi, Brindusa; Catrinescu, Cezar; Dumitriu, Emil; Ungureanu, Adrian; Alamdari, Houshang; Petit, Sabine; Royer, Sébastien
Abstract: A melt infiltration strategy allows the encapsulation of transition metal (oxide) nanoparticles in the intra‐wall pores of SBA‐15 supports, providing ultrafine particles that are stable at high temperatures (up to 900 °C, oxidizing–reducing atmospheres). Selective localization of transition metal (oxide) precursor in the secondary pores is achieved in the presence of organic structure‐directing agent occluded in the intra‐wall pores, and by applying an intermediate diffusion step during preparation. Abstract : Ultra‐fine (≤2 nm) transition metal (oxide) nanoparticles (NPs), presenting unusual thermal stability, are obtained by a melt infiltration strategy that allows selective diffusion of precursors into the intra‐wall pores of a mesoporous scaffold. Catalytic hydrogenation experiments highlight the outstanding activity of the ultra‐fine, thermally stable metal (oxide) NPs.